Lesions in two Escherichia coli type 1 pilus genes alter pilus number and length without affecting receptor binding. - Russell, P W (1992)
We describe the characterization of two genes, fimF and fimG (also called pilD), that encode two minor components of type 1 pili in Escherichia coli. Defined, in-frame deletion mutations were generated in vitro in each of these two genes. A double mutation that had deletions identical to both single lesions was also constructed. Examination of minicell transcription and translation products of parental and mutant plasmids revealed that, as predicted from the nucleotide sequence and previous reports, the fimF gene product was a protein of ca. 16 kDa and that the fimG gene product was a protein of ca. 14 kDa. Each of the constructions was introduced, via homologous recombination, into the E. coli chromosome. All three of the resulting mutants produced type 1 pili and exhibited hemagglutination of guinea pig erythrocytes. The latter property was also exhibited by partially purified pili isolated from each of the mutants. Electron microscopic examination revealed that the fimF mutant had markedly reduced numbers of pili per cell, whereas the fimG mutant had very long pili. The double mutant displayed the characteristics of both single mutants. However, pili in the double mutant were even longer than those seen in the fimG mutant, and the numbers of pili were even fewer than those displayed by the fimF mutant. All three mutants could be complemented in trans with a single-copy-number plasmid bearing the appropriate parental gene or genes to give near-normal parental piliation. On the basis of the phenotypes exhibited by the single and double mutants, we believe that the fimF gene product may aid in initiating pilus assembly and that the fimG product may act as an inhibitor of pilus polymerization. In contrast to previous studies, we found that neither gene product was required for type 1 pilus receptor binding.